2016
DOI: 10.1007/s10603-016-9327-7
|View full text |Cite
|
Sign up to set email alerts
|

Do Target Groups Appreciate Being Targeted? An Exploration of Healthy Eating Policy Acceptance

Abstract: The impact of healthy eating policies does not meet policy makers' expectations; as such, better targeting and stakeholder support could improve their effectiveness. This research aims to identify whether a target group (the group affected by the policy measure) has higher acceptance levels or not. The study compared acceptance among citizens from the target with a matching nontarget group, based on data from an online survey on citizens' support of healthy eating policies conducted among 3,003 adult responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
6
0
1
Order By: Relevance
“…and themes identified in the follow-up open-ended question about the motives for the response: Uruguayan citizens aged 18-75 years (n 1416), 61 % female, who responded to an online survey about nutritional warnings as front-of-pack labels, 2017 (Table 3). This result is in accordance with previous studies conducted in Europe that report that nutrition labelling is typically one of the policies with the highest citizen acceptance (30,31) . Nutrition labelling has also been regarded as one of the policies with the lowest stakeholder opposition (41) , which enables quick policy action.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…and themes identified in the follow-up open-ended question about the motives for the response: Uruguayan citizens aged 18-75 years (n 1416), 61 % female, who responded to an online survey about nutritional warnings as front-of-pack labels, 2017 (Table 3). This result is in accordance with previous studies conducted in Europe that report that nutrition labelling is typically one of the policies with the highest citizen acceptance (30,31) . Nutrition labelling has also been regarded as one of the policies with the lowest stakeholder opposition (41) , which enables quick policy action.…”
Section: Discussionsupporting
confidence: 93%
“…Citizen perception of public policies is shaped by sociodemographic variables ( 30 , 31 ) . In the specific case of nutrition labelling, prior research has shown that gender, age and socio-economic level modulate the ability of FOP labels to modify food choices due to differences in nutrition knowledge and the relative importance attached to the nutritional composition of foods in daily purchase decisions ( 32 , 33 ) .…”
mentioning
confidence: 99%
“…In a cross‐European study, Aschemann‐Witzel et al . (2016) showed that target groups directly affected by health policy measures are more supportive than non‐target groups in terms of healthy eating initiatives involving banning vending machines in schools, education campaigns in workplaces, food labelling, and price subsidies. Regardless of explicit support from different stakeholders (e.g., parents, students, school authorities, and business managers) vis‐à‐vis the nutritional quality of products sold through vending machines (Murnan et al ., 2006; Carrad et al ., 2015), the proportion of healthy items offered through these channels, both at public and private locations, is still limited (Webber et al ., 2007; Pasch et al ., 2011; Nowak et al ., 2012; Royo‐Bordonada and Martínez‐Huedo, 2014; Raposo et al ., 2016; Vine et al ., 2017; Monroy‐Parada et al ., 2018).…”
Section: Review Findingsmentioning
confidence: 99%
“…Mayoritas studi tentang pemahaman masyarakat terhadap kebiasaan makan yang sehat umumnya terfokus pada mengkontraskan persepsi dalam masyarakat terhadap panduan makanan sehat yang dikeluarkan oleh institusi kesehatan (Aktaç et al, 2019;Aschemann-Witzel, Bech-Larsen, & Capacci, 2016;Ducrot et al, 2017;Goh et al, 2009). Ini logis, sebab, secara umum, persepsi umum di masyarakat mengenai kebiasaan makan yang sehat sepertinya dipengaruhi oleh panduan makan sehat itu yang umumnya merekomendasikan sayuran dan buah, daging, pembatasan lemak dan garam, dan keragaman jenis makanan (Donato, 2006;Raine, 2005;Taylor et al, 2005).…”
Section: Pendahuluanunclassified